High fidelity quantum gates of trapped ions mediated by a dissipative bus mode - Haddadfarshi,F; Mintert (New Journal of Physics, 2016)
We describe entangling quantum gates for trapped ions mediated bya dissipative bus mode and show that suitably designed, polychromatic controlpulses decrease ion-phonon entanglement substantially while maintaining the mediatedinteraction. In particular for multi-qubit gates this yields a signi cant improvement ingate performance.